(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In this era, there is a certain need of keeping all the details digital, with increasing use of technology and need to compete with the outside world one should have some applications where he can store his data. With a great demand of medicines, one could not cope up with this fast world in keeping his data manually. This paper presents an application through python which help us to record data about the medicine. Whenever a person needs, he can change the data, update it, or delete it which help the person to get data about medicines. This application will help to keep record of all the medicines in a good manner and any type of medicine can be searched easily with exact details about that item. It can help to easily update the stock of the medicines available. On seeing any prescription one can search the medicine easily that is it available or not.